PENGARUH MEDIA EDUCAPLAY TERHADAP MOTIVASI BELAJAR DAN KETERAMPILAN PEMECAHAN MASALAH SISWA PADA MATERI PENDIDIKAN AGAMA ISLAM DAN BUDI PEKERTI - Yuyun Nailufar; Muhajir Muhajir; Sucipto Sucipto (Universitas Muhammadiyah Ponorogo, 2026)
This study aimed to determine the effect of Educaplay media on students' learning motivation and problem-solving skills in the Islamic Education and Ethics subject at SMK Negeri 3 Sampang. This study employed a quantitative approach using a quasi-experimental non-equivalent control group design. The research subjects consisted of 60 tenth-grade students, divided into an experimental group and a control group. The instruments used included a learning motivation questionnaire and a problem-solving skills test. Data were analyzed using a paired sample t-test and a Multivariate Analysis of Variance (MANOVA). The results indicated that the use of Educaplay media had a significant effect on students' learning motivation. Additionally, it had a significant effect on students' problem-solving skills. Simultaneously, the MANOVA results revealed that Educaplay media had a combined effect on both students' learning motivation and problem-solving skills in the Islamic Education and Ethics subject at SMK Negeri 3 Sampang. Based on these findings, it can be concluded that Educaplay is an effective interactive learning medium for improving students' learning motivation and problem-solving skills. Therefore, Educaplay is recommended as an alternative instructional medium for Islamic Education and Ethics in schools.